Game Characters as Narrative Devices. A Comparative Analysis of Dragon Age: Origins and Mass Effect 2 - Jørgensen, Kristine (Eludamos: Journal for Computer Game Culture, 2010)
This article presents a comparative analysis of how characters are used as narrative tools in Bioware’s computer role-playing games Dragon Age: Origins (2009) and Mass Effect 2 (2010). The analysis aims to demonstrate how sophisticated narrative features can be integrated in gameplay through the development of interesting characters. Using a comparative analysis, the author shows that the two games’ have different approaches to using characters as narrative tools within the same genre, while also incorporating these narrative features tightly into gameplay. Central to the argument is the idea that presenting the player as protagonist is not necessarily the most fruitful approach to narrative experiences in games, and that narrative coherence may be better established and maintained through letting non-player characters carry the weight of narrative progression.